The decline in employment of people with disabilities : a policy puzzle - Stapleton, David C.; Burkhauser, Richard V. (W.E. Upjohn Institute for Employment Research, 2003)
Annotation This volume reports on the employment decline of working-age people with disabilities. The contributors provide documentation of the decline, an evaluation of its conflicting causes, and the implications for public policy.